Are mobile botnets a possible threat? The case of SlowBot Net. Issue 58 (May 2016) - Farina, Paolo; Cambiaso, Enrico; Papaleo, Gianluca; Aiello, Maurizio
Graphical Abstract: Abstract: In virtue of the large-scale diffusion of smartphones and tablets, a possible exploitation of such devices to execute cyber-attacks should be evaluated. This scenario is rarely considered by cyber-criminals, since mobile devices commonly represent a target of attacks, instead of an exploitable resource. In this paper we analyze the possibility to execute distributed denial of service attacks from mobile phones. We introduce SlowBot Net, a botnet infrastructure designed to involve mobile agents, and we compare it with Low-Orbit Ion Cannon (also called LOIC), a well-known botnet adopted by cyber-hacktivists on the Internet. Results prove that SlowBot Net requires fewer resources to the attacker and it is effectively deployable on mobile nodes. Since research related to mobile botnets is still immature, the proposed work should be considered a valuable resource enriching the cyber-security field.